PROTOTYPE SISTEM INFORMASI ADMINISTRASI BERBASIS WEB DI SEKRETARIAT DPRD KABUPATEN AGAM - , Rospiyarni Rosa, Dr. Ir. Lukito Edi Nugroho, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Agam district parliament Secretariat as one of the executive agency which has duties and functions of parliament to support activities include correspondence, reports of meetings and a working visit and a schedule of monthly activities. Parliament as the legislature have a strategic position in the life of the state. Optimal support of the Secretariat of the Parliament to be essential to the performance of parliament, so the need to design an information system administration activity Parliament includes incoming mail, outgoing mail, reports and schedules. The prototype system is briefly described the administrative information system in question. The purpose of this prototype design also makes it easy for Parliament to communicate with the public based on the latest information and be widely accessible anywhere and anytime. It also strongly supports the level of public confidence in the performance of Parliament because they can communicate directly via email and access the activities and reports of activities parliament. In this study the design of a prototype web-based administrative information systems in Agam district parliament Secretariat can be accessed without attachment to the time and place. The final results of this study is easier for users to access information relating to the performance of parliament. Prototype is designed using UML tools paradigm "object oriented" and use the programming language PHP, and MySQL as database system.